PENYELENGGARAAN BADAN USAHA MILIK DAERAH BERDASARKAN UNDANG UNDANG NOMOR 24 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Heriyanto; Mustofa (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
The urgency to review and improve the juridical basis for the management of Regional-Owned Enterprises in relation to the principle of a unitary state as mandated by Law Number 23 of 2014 concerning Regional Government, particularly in the implementation of the authority of the Situbondo Regional Government of East Java in an effort to improve the management paradigm of the Pasir Regional Company. White is absolutely necessary so that it remains synergistic and does not conflict with national policies. This study aims as a material for a juridical study on the synergy of the implementation of Regional-Owned Enterprises in accordance with the mandate of Law 24/2014 on regional governance. And aims to provide a juridical analysis of the implementation of Regional Regulation Number 9 of 2014 concerning White Sand Regional Companies in accordance with the mandate of Law Number 24 of 2014 concerning Regional Government. In this study using a juridical normative legal research method with a statute approach, namely by analyzing the issues or problems in this study, with a test stone of applicable laws and regulations. So that the results of this study serve as an alternative reference in legal studies. regional government and make the basis on the basis of academic considerations for local governments in determining prolegda policies to make adjustments to regional regulations with higher hierarchical regulations.